Perancangan Model Pengembangan Kinerja Daya Saing Klaster Industri Minyak Dan Gas Bumi Di Jawa Timur - Hanoum, Syarifa; Suwignjo, Patdono; Wirjodirdjo, Budisantoso; Juwita P, Devinata (Department Industrial Engineering, University of Muhammadiyah Malang, 2011)
Oil and gas industry is a sector that has a vital strategic role on national development. East Java is one of the province in Java that has an enourmous potential on oil and gas and has not been optimally explored. Industrial cluster is an industrial development concept that comphrehensively organize the relationship and behaviour of stakeholder in industry so that they can co-operate to increase the competitiveness of the industry. The increasing of industrial competitiveness is supported by completeness and contribution of each industry in oil and gas industial cluster in each java by identifying the behaviour of stakeholder and system in this sector which is described in stakeholder model and value chain model. In this research, lubricant industrial cluster is used as an embryo for developing oil and gas industrial cluster. The complexity of the system in terms of system behaviour will be presented in a dynamic system model, which will make it possible to identify the influence between each variables.The Porter’s Diamond model is adapted to model the behaviour of the competitiveness. The result of this research showed that in increasing the industrial cluster competitiveness some variables are significantly influencing then the others.